Kajian Pemindahan Rute Penerbangan Bandar Udara Terhadap Kepuasan dan Nilai Pelanggan - Rd Arasheila Ramanya; Fauzia Mulyawati; Sudarsono Sudarsono (Universitas Batanghari Jambi, 2023)
After switching flight paths in July 2019 for both domestic and international flights, Husein Sastranegara Airport in Bandung was replaced by West Java International Airport in Majalengka. In comparison to Husein Sastranegara Airport, several airlines operating at Kertajati Airport saw a drop in passenger traffic. A survey was carried out in this study using a questionnaire that was given to 113 participants. The statistical package for social science (SPSS) application and structural equation modeling (SEM) with SmartPLS will subsequently be used to process the survey results. Data analysis revealed that airport accessibility (AA), terminal facilities (TF), and customer value are all positively impacted by the characteristics that contribute to an improvement in customer satisfaction (CS) (CV). Airport Accessibility is by far the most important of these characteristics, which serve as the standards by which travelers select their flights, according to the poll. The calculation's outcome demonstrates that rcount exceeds rtable. Customer satisfaction (CS) R-Count 0.889 and R-Table 0.183, Terminal facilities (TF) R-Count 0.885 and R-Table 0.183, Service innovation (SI) 0.856 and R-Table 0.183, and Customer Value R-Calculate 0.926 and R-Table 0.183 are the results using SPSS for these variables. From the experimental findings, it can be inferred that the supply of different services and amenities at the airport affects consumer happiness.